Application of life cycle thinking towards sustainable cities: A review. (10th November 2017) - Petit-Boix, Anna; Llorach-Massana, Pere; Sanjuan-Delmás, David; Sierra-Pérez, Jorge; Vinyes, Elisabet; Gabarrell, Xavier; Rieradevall, Joan; Sanyé-Mengual, Esther
Abstract: Defining sustainable cities is not straightforward. The main issues involved in urban sustainability are buildings, energy, food, green areas and landscape, mobility, urban planning, water and waste; and their improvement is promoted through different strategies. However, a quantitative method, such as life cycle thinking (LCT), is essential to evaluating these strategies. This paper reviews LCT studies related to urban issues to identify the main research gaps in the evaluation of these improvement strategies. The review identifies the main sustainability strategies associated with each urban issue and compiles articles that deal with these strategies through LCT, including environmental life cycle assessment (LCA), life cycle costing (LCC), social LCA (S-LCA) and life cycle sustainability assessment (LCSA), as well as integrated analyses with combined tools. Water, waste and buildings are the urban issues that accounted for a larger amount of studies. In contrast, a limited number of papers assessed urban planning and energy (excluding energy in buildings). Strong interrelations among urban issues were identified, most of them including water. In terms of methods, 79% of the studies exclusively applied life cycle tools (i.e., LCA, LCC, S-LCA or LCSA). Within this group, the environmental dimension was the focus of 84% of the papers. Single environmental indicators (e.g., global warming) were common in 20% of the analyses, highlighting the need to integrate more impact categories to prevent trade-offs. In the field of social and sustainability assessment, there is a need for methodological advances that foster their application in urban areas. Further research should cover the thematic and methodological gaps identified in this paper, such as developing models that assess complex urban issues, generating comprehensive LCT studies and promoting multi-indicators. Life cycle tools might benefit from revising the methodology with stakeholders to optimize the understanding and communication of life cycle results for policy- and decision-making processes. Highlights: We identified strategies promoted to achieve urban sustainability. Based on urban issues, we reviewed the life cycle studies conducted for each strategy. Water, waste and buildings were widely covered from a life cycle standpoint. Urban planning and energy still need to be included in these assessments. There is a lack of social studies and more methodological advancements are needed.